The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1002/(sici)1520-6343(1997)3:2<161::aid-bspy9>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

A novel diagnostic test for arthritis: Multivariate analysis of infrared spectra of synovial fluid

Abstract: Fourier transform infrared spectroscopy has been applied to the investigation of synovial fluids (SFs) aspirated from arthritic joints. Significant differences, related to differences in the composition of the fluid as a result of the disease processes, were found between spectra of SFs from joints affected by rheumatoid arthritis, osteoarthritis, spondyloarthropathies, and meniscal injuries. Linear discriminant analysis with leave‐one‐out cross validation was used to classify 239 SF film spectra obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 11 publications
0
60
2
1
Order By: Relevance
“…), and the environment of the bond. In the last fifteen years, IR spectroscopists have taken advantage of this molecular information, in combination with pattern recognition/classification methods, to explore its potential as a powerful tool for the diagnoses of various diseases based upon the spectra of biological fluids, including amniotic fluid, lipid profiles, synovial fluid, saliva and gingival crevicular fluid to predict fetal lung maturity (Liu et al, 1998), diagnose heart disease (Liu et al, 2002) and rheumatoid arthritis (Eysel et al, 1997), assess global diabetes-associated alterations and evaluate periodontal inflammations (Xiang et al, 2010), respectively. The IR spectrum of saliva and GCF is a rich source of information regarding the oral cavity and associated inflammation.…”
Section: Molecular Fingerprinting Of Gingivitis Gcf By Mir Spectroscopymentioning
confidence: 99%
“…), and the environment of the bond. In the last fifteen years, IR spectroscopists have taken advantage of this molecular information, in combination with pattern recognition/classification methods, to explore its potential as a powerful tool for the diagnoses of various diseases based upon the spectra of biological fluids, including amniotic fluid, lipid profiles, synovial fluid, saliva and gingival crevicular fluid to predict fetal lung maturity (Liu et al, 1998), diagnose heart disease (Liu et al, 2002) and rheumatoid arthritis (Eysel et al, 1997), assess global diabetes-associated alterations and evaluate periodontal inflammations (Xiang et al, 2010), respectively. The IR spectrum of saliva and GCF is a rich source of information regarding the oral cavity and associated inflammation.…”
Section: Molecular Fingerprinting Of Gingivitis Gcf By Mir Spectroscopymentioning
confidence: 99%
“…Consider the classification problem of assigning the object , , into one of predefined classes. The Bayes rule assigns to the class , , which maximizes the posterior probability [24] ( 5) where is the prior probability of belonging to class , and is the class probability density, i.e., the probability of object arising from class , so it requires that (6) In practice, the class probability densities are often assumed to follow a multivariate normal distribution and can be written as (7) If indicates that is from class and the total number of samples in in training set, then (8) is the mean vector of class , and (9) is the mean vector of class . Typically, and are calculated form the training data.…”
Section: ) Choice Of the Discriminant Criterionmentioning
confidence: 99%
“…The advantages of their methods are that combined application of infrared spectroscopy and pattern recognition principles provided a rapid (of the order of minutes), nonsubjective method for the diagnosis of the major forms of arthritic disorders. An important technical advantage is that the method requires minute volumes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) of synovial fluid. Although these studies demonstrated that IR analysis of SF could aid in differential diagnosis of arthritic disorders, some limitations exist.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrational spectroscopy has attracted a lot of attention in medicine because it can serve as an auxiliary method in the diagnosis of certain diseases, being a non-invasive technique [5,10,11,24]. This technique has several advantages, such as sensitivity, speed and the reagent-free nature of the measurement.…”
Section: Introductionmentioning
confidence: 99%